2020
DOI: 10.1111/jop.13038
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke modulates binding of the transcription factor MZF1 to the VEGF promoter and regulates VEGF expression in dependence of genetic variation SNP 405

Abstract: Background Vascular endothelial growth factor (VEGF) affects carcinogenesis of the upper aerodigestive tract. Cigarette smoke (CSE) influences VEGF‐gene regulation. The single nucleotide polymorphism +405 G/C (SNP +405 G/C) and the transcriptional factor (TF) myeloid zinc finger 1 (MZF1) are endogenic regulators of the VEGFpromoter as the polymorphism 405 potentially affects binding of the transcription factor MZF1. Therefore, this in vitro study analysed cancer cells of the upper aerodigestive tract after CSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, MZF1 can also function as a tumor suppressor that, for instance, represses MMP2 in cervical cancer [ 34 ] and mediates oncogene-induced senescence [ 35 ]. Furthermore, MZF1 is also vital in a protumorigenic microenvironment by activating the osteopontin ( OPN ) gene in mesenchymal stem cells (MSC), leading to transformation into cancer-associated fibroblasts (CAF) [ 36 ] and the VEGF gene in tumor endothelial cells (TEC) [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, MZF1 can also function as a tumor suppressor that, for instance, represses MMP2 in cervical cancer [ 34 ] and mediates oncogene-induced senescence [ 35 ]. Furthermore, MZF1 is also vital in a protumorigenic microenvironment by activating the osteopontin ( OPN ) gene in mesenchymal stem cells (MSC), leading to transformation into cancer-associated fibroblasts (CAF) [ 36 ] and the VEGF gene in tumor endothelial cells (TEC) [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our previous findings have shown that cigarette smoking combine with genetic variations to jointly affect bladder cancer risk 8 . Importantly, cigarette smoking and genetic variant can collaboratively regulate downstream gene expression by influencing transcription factor binding and DNA methylation 36,37 . Our findings have now revealed that the combination of cigarette smoking and rs2273058 may also regulate CRNKL1 expression through m 6 A modification and its recognition.…”
Section: Discussionmentioning
confidence: 64%
“…8 Importantly, cigarette smoking and genetic variant can collaboratively regulate downstream gene expression by influencing transcription factor binding and DNA methylation. 36,37 Our findings have now revealed that the combination of cigarette smoking and rs2273058 may also regulate CRNKL1 expression through m 6 A modification and its recognition. Therefore, our study contributes to the existing knowledge about how cigarette smoking interacts with genetic factors to affect bladder disease risk.…”
Section: Discussionmentioning
confidence: 79%
“…However, MZF1 can also function as a tumor suppressor that, for instance represses MMP2 in cervical cancer [34] and mediates oncogene-induce senescence [35]. Furthermore, MZF1 is also important in a protumorigenic microenvironment by activating osteopontin gene in mesenchymal stem cells, leading to transformation into cancer-associated fibroblasts (CAF) [36] and VEGF gene in tumor endothelial cells [37].…”
Section: Introductionmentioning
confidence: 99%